"Nothing Fits Exactly": Experiences of Asian American Parents of Twice-Exceptional Children. (July 2018) - Park, Soeun; Foley-Nicpon, Megan; Choate, Alyssa; Bolenbaugh, Mallory
Parents of high-ability students with disabilities (i.e., twice-exceptional) play a crucial role in their children's home and educational environments. In addition, parents' sociocultural contexts, including race and ethnicity, can influence their parenting practice. We conducted interviews with 10 Asian American parents from diverse ethnic backgrounds and analyzed the interview transcripts by using a phenomenological framework and general inductive approach. Themes identified included the parents' recognition of and reaction to twice-exceptionality, challenges and efforts in supporting their children, and perception of their sociocultural contexts in relation to parenting practices. The Asian American parents in this study developed resilient parenting styles and persistent advocacy efforts as they navigated the complex characteristics of twice-exceptionality within their multilayered cultural contexts. Findings are particularly important for practitioners and educators who work with Asian American parents and/or high-ability children with disabilities to better address their complex needs.